Edukasi Kesehatan Tentang Pemberian Suntik Imunisasi Lengkap di Desa Ujong Rimba Kec. Darul Hikmah Kab. Aceh Jaya - Diana Lestari; Meylissa Meylissa; Yuliana Abty (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
Immunization is an effective means of preventing infectious diseases. However, there are still people who do not understand the importance of complete immunization for children. This community service aims to increase public knowledge and awareness regarding the importance of immunization through health education activities. The methods used are outreach, discussion, and question and answer sessions to the community in the target area. The results of the activity show an increase in public understanding of the benefits of immunization as well as an increase in immunization coverage for children. It is hoped that this health education can be sustainable in order to achieve optimal immunization coverage.